Increased oxygenation in the non-contracting forearm muscle during contralateral skillful hand movement - Asahara, R.; Ishii, K.; Okamoto, I.; Sunami, Y.; Hamada, H.; Kataoka, T.; Ohshita, W.; Watanabe, T.; Matsukawa, K. (Experimental Physiology, 2020)
What is the central question of this study?